Estate landscapes in Gelderland: Government interventions, past and present (Bulletin KNOB, 2021)
The Province of Gelderland has long boasted a large number of country houses and landed estates, which over time coalesced into estate landscapes around the historical capitals of the Duchy of Guelders quarters of Nijmegen, Arnhem and Zutphen.Rapidly increasing urbanization from the end of the nineteenth century onwards threatened the coherence and accessibility of these landscapes. Gelderland’s largest cities, Arnhem and Nijmegen, watched in dismay as many country houses and landed estates fell victim to subdivision and development. In response they started to buy up portions of that estate landscape to ensure that they would remain available to city dwellers. In addition, the ‘safety net’ provided by newly established nature and landscape organizations, in particular Natuurmonumenten and Geldersch Landschap & Kasteelen, also contributed to preservation and permanent accessibility by offering landed families the opportunity to keep their estate intact, albeit no longer under their ownership.Similar motives – the need to preserve attractive, accessible walking areas for the increasingly urbanized society – underpinned the government’s introduction of the Nature Conservation Act in 1928. The Act was invoked more frequently in Gelderland than in any other province. It promoted the opening up of private properties as well as the preservation of the cultural value of the kind of ‘natural beauty’ to be found on landed estates.After the Second World War, in addition to resorting to the Nature Conservation Act, the owners of country houses and landed estates could avail themselves of an increasing variety of grants aimed at preserving (publicly accessible) nature, landscape and heritage, although the emphasis was firmly on nature. Estate landscapes like the Veluwezoom and the County of Zutphen were eventually safeguarded by a patchwork of different government regulations.In the twenty-first century, government policy shifted towards providing financial support for both public and private contributions to nature, landscape and heritage by country houses and landed estates. This in turn has stimulated interest in estate landscapes. Instead of individual heritage-listed estates, the focus is now on areas with multiple country house and landed estates where there are spatial tasks waiting to be fulfilled: not just the preservation of natural beauty for outdoor recreation, but also spatial articulation, climate change adaptation, increased biodiversity and sustainable agriculture. Interest in design, both past and present, has burgeoned thanks to this development.